Manajemen Madrasah dalam Membangun Budaya Literasi Peserta Didik di Madrasah Aliyah Negeri 2 Lombok Timur - Apnadi, Apnadi; Sulhan, Ahmad; Muhtar, Fathurrahman (AS-SABIQUN, 2024)
Literacy culture can be a reflection of the progress of the nation. Literacy culture can also be an indicator that distinguishes primitive society from civilized society. A nation whose literacy is still low will experience a gloomy civilization. The purpose of this study was to determine the ability, and management of madrasahs and implications in Basic Literacy, especially the reading aspect of students at Madrasah Aliyah Negeri (MAN) 2 Lombok Timur. In this study, documentation, observation, and interviews are the methods used to collect data. The results of the study are literacy activities that have begun to grow and develop at MAN 2 Lombok Timur, becoming a special attraction to make MAN 2 Lombok Timur a research location. This is related to Meidiawati's view that several things can be done to build a culture of literacy, namely fostering interest in reading, subsidizing or providing books or reading materials, optimizing the existence of libraries, appreciating written works, and government political support. madrasah management in building a culture of literacy for students at MAN 2 Lombok Timur. Management is related to efforts to plan, organize, mobilize, and control all aspects of activities in realizing the development of a culture of literacy. As part of the management carried out at MAN 2 East Lombok to build a culture of literacy, namely Building a joint commitment, Forming a literacy team, Monitoring and controlling the implementation of commitments, and Providing appreciation for active and high-achieving students (4-M). The management implemented at MAN 2 East Lombok can improve the ability and enthusiasm of students in literacy, improve the quality of literacy results, increase the number of literacy enthusiasts, and foster student awareness in cultivating literacy in their daily lives.